The role of anti-aquaporin 4 antibody in the conversion of acute brainstem syndrome to neuromyelitis optica - Cheng, Chen; Jiang, Ying; Lu, Xiaodong; Gu, Fu; Kang, Zhuang; Dai, Yongqiang; Lu, Zhengqi; Hu, Xueqiang (BioMed Central, 2016)
Background: Acute brainstem syndrome (ABS) may herald multiple sclerosis (MS), neuromyelitis optica (NMO), or occur as an isolated syndrome. The aquaporin 4 (AQP4)-specific serum autoantibody, NMO-IgG, is a biomarker for NMO. However, the role of anti-AQP4 antibody in the conversion of ABS to NMO is unclear.